Suelos y nutricion de la planta - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
Advances in research of the soil and plant nutrition section of CIAT's Cassava Program in 1981 are given regarding symptoms of Ca and S deficiency, germplasm screening for adaptation to high acidity and/or low P; effect of fertilization (long-term fertility); level and time of K application; effect of nutrient status of planting material on the growth and yield of the crop; external P requirements; fertilizer response as related to soil fertility; and response to mycorrhizal inoculation. Critical levels were 0.27 and 0.3 percent for S and Ca, resp., DM production being severely reduced below these levels. Different var. were grouped according to an adaptation index into 3 categories (highly adapted, adapted, and nonadapted to low-P soils) and according to variation in yield. Those var. with greatest efficiency of P uptake were also more tolerant to acid soils. Annual application of N-P-K increased yields from 20 to 43 t/ha. The application of 168 kg K/ha gave the highest root yield in var. M Ven 77, while the application of 84 kg k/ha increased its starch content. Root yield was closely related to total P content of stakes, reaching a max. at about 15 mgP/stake. Max. external P requirements were calculated to be 0.027 and 0.030 ppm for CMC-40 and M Col 1684, resp. Yield response of several cv. to different levels of N, P, and K application in 10 locations varied according to soil type. Response to mycorrhizal inoculation depends on P content in planting material and existence of native mycorrhizal populations; when rooted plantlets with little P reserves were used, the response was more marked. (CIAT)